2016
DOI: 10.1093/cid/ciw208
|View full text |Cite
|
Sign up to set email alerts
|

Acute Appendicitis in Children Is Associated With a Local Expansion of Fusobacteria

Abstract: These results indicate that the appendiceal niche harbors distinct microbial populations that likely contribute to the pathogenesis of appendicitis, which may one day be leveraged to improve the diagnosis and/or treatment of patients with AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 37 publications
4
48
1
2
Order By: Relevance
“…The LEfSe analysis found that premature infants in BM group and the FM group had only significant differences among the three bacteria. Fusobacterium is an anaerobic Gram-negative pathogen that causes appendicitis in children (Rogers et al, 2016) and is found in murine model to result in premature (Han et al, 2004). Bacteria from the Prevotella family had been found to be higher in formula fed infants than breast fed infants (Holgerson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The LEfSe analysis found that premature infants in BM group and the FM group had only significant differences among the three bacteria. Fusobacterium is an anaerobic Gram-negative pathogen that causes appendicitis in children (Rogers et al, 2016) and is found in murine model to result in premature (Han et al, 2004). Bacteria from the Prevotella family had been found to be higher in formula fed infants than breast fed infants (Holgerson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…37,40,41,[44][45][46][47] Transmission routes were associated with food borne transmission 35,39 and fomite transmission; 37,47 Measures for control of infectious diseases seem to be effective to prevent appendicitis. 47 Since 2009, new studies have provided compelling evidence of an association between appendicitis and the presence of Fusobacteria in the appendices, [64][65][66][67][68][69] and Fusobacteria were also found in clustering patients we reported in 2012. 38 Study of cluster/outbreak will provide new methods to confirm causal association between microbiota and different entity of appendicitis.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, several trials have focused on the non-operative treatment for AA [18,22] . Studies suggested that different treatment strategies should be selected according to the type of AA: simple appendicitis should be the preferred antibiotic conservative treatment, while complicated appendicitis requires appendectomy in most cases [6,15] . Children appendix is not a non-functional organ left in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical presentation, Pediatric Appendicitis Score (PAS), ALVARADO score, Computed tomography, ultrasound and blood tests, may be helpful in diagnose of AA, but it is difficult to confirm the type of appendicitis (simple or complicated appendicitis) [3][4][5] . Been able to diagnose uncomplicated vs. complicated appendicitis allows the surgeon to choose the best surgical approach ranging from antibiotics and delayed appendectomy to laparotomy [6] . Perforated appendicitis after surgery requires antibiotic mono or combination therapy [7] .…”
Section: Introductionmentioning
confidence: 99%